Hello!
When we are dividing polynomials, we need to find their common factors.
Looking at the first term in the dividend with the divisor, it's common factor is 2x.
We would multiply 2x by the binomial (x + 2) and subtract it.
2x(x + 2) = 2x² + 4x
2x² + 10x + 7 - (2x² + 4x)
2x² + 10x + 7 - 2x² - 4x = 6x + 7
We are left with 6x + 7. Now, we need to find the common factor in 6x, which is 6, and multiply 6 by the divisor and subtract.
6(x + 2) = 6x + 12
6x + 7 - (6x + 12)
6x + 7 - 6x - 12 = -5
Therefore, the quotient is 2x + 6, with a remainder of -5.